Fipronil degradation kinetics and resource recovery potential of Bacillus sp. strain FA4 isolated from a contaminated agricultural field in Uttarakhand, India. (August 2021) - Bhatt, Pankaj; Rene, Eldon R.; Kumar, Alagarasan Jagadeesh; Gangola, Saurabh; Kumar, Govind; Sharma, Anita; Zhang, Wenping; Chen, Shaohua
Abstract: This study investigates the potential role of Bacillus sp. FA4 for the bioremediation of fipronil in a contaminated environment and resource recovery from natural sites. The degradation parameters for fipronil were optimized using response surface methodology (RSM): pH - 7.0, temperature - 32 °C, inocula - 6.0 × 10 8 CFU mL −1, and fipronil concentration - 50 mg L −1 . Degradation of fipronil was confirmed in the mineral salt medium (MSM), soil, immobilized agar discs, and sodium alginate beads. The significant reduction of the half-life of fipronil suggested that the strain FA4 could be used for the treatment of large-scale fipronil degradation from contaminated environments. The kinetic parameters, such as q max, K s, and K i for fipronil degradation with strain FA4, were 0.698 day −1, 12.08 mg L −1, and 479.35 mg L −1, respectively. Immobilized FA4 cells with sodium alginate and agar disc beads showed enhanced degradation with reductions in half-life at 7.83 and 7.34 days, respectively. The biodegradation in soil further confirmed the degradation potential of strain FA4 with a half-life of 7.40 days as compared to the sterilized soil control's 169.02 days. The application of the strain FA4 on fipronil degradation, under different in vitro conditions, showed that the strain could be used for bioremediation and resource recovery of contaminated wastewater and soil in natural contaminated sites. Graphical abstract: Image 1 Highlights: A Bacillus sp. FA4 capable of degrading fipronil was isolated and characterized. Fipronil degradation was observed with strain FA4 in mineral salt medium and soil. Immobilizing FA4 in sodium alginate and agar disc accelerated fipronil degradation. FA4 can be applied in-situ for remediating fipronil contaminated soil environments.